KEBIJAKAN PEMERINTAH SURABAYA DALAM MENANGANI BERITA HOAX (Studi kasus di kota Surabaya) - Pitri Megasari (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
Abstract: This paper discusses how government policies in counteracting hoax news in the community through social media. Sometime lately more rampant news about the spread of fake news or hoaxes through online social media such as Twitter, Facebook, Instagram and YouTube. The formulation of the problem here is how the Surabaya government policy to overcome or handle the existence of false news or hoaxes in the Surabaya community. The research method for this type of research is qualitative. The data used are qualitative data, expressed in words or sentences. This false information or hoax was made deliberately because it was to influence the public because of the increasingly widespread stimulant factors such as social and political issues. Social media is now widely used to negative things like one of the accounts that spread hoax information just to increase the popularity of the account or want to be viral by spreading hoax news. Social media makes it easier for us to interact with many people and easier to convey information. But this social media makes a lot of people addicted and many social groups appear that deviate from the norms that exist in the Surabaya city government trying continuously to deal with fake news or hoaxes that are widely spread among the citizens of Surabaya.Keywords: Government Policy, Hoax News, Society